2005
DOI: 10.3201/eid1111.050575
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Human Papillomavirus Screening among Older Women

Abstract: HPV-negative women >50 years of age still require cervical screening

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 29 publications
0
35
1
3
Order By: Relevance
“…New HPV infections can be acquired at any age [46,47] and the prevalence of infection is greatest (approximately 20%) in women less than 25 years of age [14]. The incidence of oncogenic HPV infection is around 5% in women 25-55 years of age [48].…”
Section: Risk Of Hpv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…New HPV infections can be acquired at any age [46,47] and the prevalence of infection is greatest (approximately 20%) in women less than 25 years of age [14]. The incidence of oncogenic HPV infection is around 5% in women 25-55 years of age [48].…”
Section: Risk Of Hpv Infectionmentioning
confidence: 99%
“…Several other factors are associated with the development of cervical cancer following oncogenic HPV infection [26,51]. These factors include environmental factors like smoking, sexual exposure especially for early onset of sex (coitarche) and high parity [46]. The other factors are hormonal, like in long-term use of oral contraceptives and immunosuppressive factors such as HIV, transplant recipients and long-term systemic steroid use [36,39].…”
Section: Co-factors That Increase the Risk Of Progress To Cervical Camentioning
confidence: 99%
“…De même, 5,1 % des hommes (UK) âgés de 45 à 59 ans ont eu plus de deux partenaires sexuels pendant une période similaire. Enfin, Grainge et al [6] montrent que 21 % des femmes de plus de 51 ans sont infectées par l'HPV pendant un intervalle de temps de trois ans (entre deux dépistages). Ce taux est, dans cette étude, supérieur à celui observé chez les patientes plus jeunes (21, 31 et 41 ans), mais les différences ne sont pas statistiquement significatives.…”
Section: L'infection Par Hpv Après 25 Ans Et Ses Conséquencesunclassified
“…Epidemiological data from the United Kingdom have shown that approximately 96% of women between the age of 21 and 51 do not have current HPV16 or HPV18 infection [25] . Older women of 51 years of age who are DNAnegative at baseline have the highest risk (21.3%) of acquiring a cervical HPV infection during a 3-year period compared to younger age groups (21 years -15.2% and 41 years -13.3%).…”
Section: Risk Of Acquiring Hpv16 or Hpv18 Infectionmentioning
confidence: 99%